THE PRACTICE OF USING INTERACTIVE MEDIA WITH AUGMENTED REALITY (AR) BASED ON STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ARTS AND MATHEMATICS) IN STUDENT LEARNING - Husni Sabil; Novferma Novferma; Silfiani Indri (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2022)
The purpose of this study was to describe the practicality of interactive learning media with augmented reality (AR) based on STEAM in learning mathematics in junior high school. This study uses the ADDIE type of research and development method. The subjects of this study were 2 schools consisting of 1 school for the experimental class (15 students) and 1 school for the control class (15 students). The number of teachers involved was 2 teachers for the class. The data collection technique used a questionnaire aimed at teachers and students. The results of the study can be concluded that STEAM-based augmented reality practicum can improve the quality of mathematics learning in junior high school. The results showed that for the individual test, namely 2 teachers who teach mathematics subjects, the percentage was 88.20%. are in the practical category, while in the small group trial, namely 15 students, the percentage of 90.24% is in the very practical category. This study implies that research results can be input for teachers to optimize media and learning approaches, one of which is the use of the STEAM approach with augmented reality media